THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, AND MOTIVATION ON THE CONSUMPTIVE BEHAVIOR OF GENERATION Z - Syarofina, Amalia Zeta; Fahmawati, Dwi Amelia; Pratama, Feryansyah; Qasidy, Muhammad Ridha Daudy; Fadhilah, Nurul (Asian Journal of Islamic Economic Studies, 2024)
In today's rapidly advancing and modern era, technological progress has a profound impact on the lives of Generation Z individuals. This generation, known for its familiarity with the digital world, enjoys the convenience of fulfilling their needs. However, this accessibility can also lead to tendencies of extravagance and consumptive behavior. This study aims to investigate the impact of financial literacy, lifestyle, and motivation on the consumptive behavior of Generation Z students at the Faculty of Economics and Business, Sultan Aji Muhammad Idris Samarinda State Islamic University. The research involved 100 students as participants, focusing on their consumptive behavior. Data were collected through questionnaires using stratified sampling techniques. The quantitative correlation method was employed, with the multiple linear regression test used for data analysis. The findings revealed a significant value of 0.000 < 0.05, indicating that financial literacy, lifestyle, and motivation collectively influence the consumptive behavior of Generation Z students at the Faculty of Economics and Islamic Business. However, when examined individually, the financial literacy variable showed a sig value of 0.301 > 0.05, and the motivation variable had a sig value of 0.143 > 0.05, suggesting no significant influence on the consumptive behavior of Generation Z. In contrast, the lifestyle variable demonstrated a sig value of 0.000 < 0.05, signifying a significant impact on the behavior of Generation Z students at the Faculty of Economics and Islamic Business